2013
DOI: 10.1124/jpet.113.208991
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Protective Agents Prevent Exacerbation of NSAID-Induced Small Intestinal Lesions Caused by Antisecretory Drugs in Rats

Abstract: Antisecretory drugs such as histamine H 2 -receptor antagonists and proton pump inhibitors are commonly used for the treatment of upper gastrointestinal mucosal lesions induced by nonsteroidal anti-inflammatory drugs (NSAIDs). However, it has recently been reported that these drugs exacerbate NSAID-induced small intestinal lesions in rats. Unfortunately, there are few effective agents for the treatment of this complication. We examined the effects of mucosal protective agents (MPAs) (misoprostol, irsogladine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Pronase alone did not exhibit an inhibitory effect on H. pylori in vitro, even at concentrations of 3.3 ϫ 10 3 mg/liter, in previous studies (data not shown), which was consistent with previous reports demonstrating that pronase did not inhibit the growth of H. pylori (11). Misoprostol is a mucosal protective agent (26). The eradication rate of the PMG was 0% (0/15), and there was a significant difference between the eradication rates of the PMG and the HPG (P ϭ 0.022).…”
Section: Discussionsupporting
confidence: 92%
“…Pronase alone did not exhibit an inhibitory effect on H. pylori in vitro, even at concentrations of 3.3 ϫ 10 3 mg/liter, in previous studies (data not shown), which was consistent with previous reports demonstrating that pronase did not inhibit the growth of H. pylori (11). Misoprostol is a mucosal protective agent (26). The eradication rate of the PMG was 0% (0/15), and there was a significant difference between the eradication rates of the PMG and the HPG (P ϭ 0.022).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported the beneficial effects of prostanoids, especially the E type of PG, against NSAID-induced small intestinal damage in experimental animals Hatazawa et al, 2006;Takeuchi et al, 2010b;Satoh et al, 2014). Furthermore, because intestinal fluid secretion is thought to hamper enterobacterial invasion, the major pathogenic event in NSAID-induced enteropathy (Takeuchi et al, 2010a), the activation of ClC-2 chloride channels may alleviate the occurrence of intestinal damage by stimulating fluid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Since the protective effect of lansoprazole was attenuated by the prior administration of tin-protoporphyrin IX (SnPP), an inhibitor of hemoxygenase (HO)-1, this action was assumed to be caused by the induction of HO-1 and carbon monoxide. Recent studies reported that antisecretory drugs such as PPIs and H 2 -RAs exacerbated the intestinal ulcerogenic response to NSAIDs such as indomethacin and naproxen, and this was attributed, at least partly, to dysbiosis of microbiota or intestinal hypermotility [41,42,43]. These findings suggest the possible risk of the co-administration of NSAIDs and antisecretory drugs; however, this treatment is known to be effective for preventing NSAID-induced gastric and duodenal damage.…”
Section: Effects Of Various Drugs On Nsaid-induced Small Intestinal Dmentioning
confidence: 99%